Correlation between Postural Stability and Functional Mobility in Patients with Knee Osteoarthritis - Hafsari, Arlinda De; Vitriana, Vitriana; Tahid, Alwin (Althea Medical Journal, 2015)
Background: Osteoarthritis (OA) is a degenerative joint disorder caused by progressive erosion of articular cartilage. The joint which is commonly affected is theknee joint. Patient with knee OA has increasing pain with decreasing postural stability, and may cause decrease infunctional mobility of the body. The aim of this study was to analyze the correlation between stability and mobility in patients with knee OA.Methods: A cross sectional study was performed to 43 patients from the Rheumatology Clinic of Dr. HasanSadikin General Hospital, Bandung, duringÂ SeptemberâOctober 2013. The âTimed Up and Goâ (TUG) test and stabillometric platform examination were performed to analyze the mobility and stability in subjects. The data were analyzed with Spearmanâs Correlation.Results: Four subjects (9.30%) had normal functional mobility, 31 subjects (72.09%) had good mobility and need no help of others in their activities, and 8 subjectsÂ (18.60%) had problems and could not stand and walk without help. This study also found 39 subjects (90.69%) had high risk of fall. The p value were 0.005 for correlation between knee OA and lateral static postural stability, 0.138 with anteroposterior static stability, 0.067 with dynamic to position of top right stability, 0.344 with dynamic to position of top left stability, 0.384 with dynamic to position of bottom left stability and 0.357 with dynamic to position of bottom right stability.Conclusions: There is a strong correlation between functional mobility with static postural stability, especially to the lateral position. [AMJ.2015;2(4):550â4]Â DOI:Â 10.15850/amj.v2n4.639